The language system and its functioning in speech - Pesina, Svetlana A.; Prosyannikova, Olga I.; Tsytsarkina, Natalia N.; Kolesnikova, Olga Yu.; Derevskova, Elena N.; Skorik, Kseniya V. (Universidade Estadual Paulista, 2021)
In the prevailing era, the problem of studying the semantics of a lexical unit faces the totality of the complex “thinking – language system – speech,” implicating the multi-segment team of scientists. Hence, he present article attempt to provide sufficient proof for the non-reflective nature of language and speech. The linguistic observation, descriptive method, comparison as a universal linguistic method are utilized to meet the aim of the study. It has been demonstrated that a linguistic form, which, as a rule, is described by the dictionary as one having many figurative metaphorical meanings, is construed as unambiguous in the language system. New meanings emerge, are arranged by the speaker and the listener in the communication process, in the frame of an utterance. Therefore, polysemy can be viewed not as a word phenomenon in the language system but as a phenomenon of an utterance in speech.